2018
DOI: 10.1002/ece3.4066
|View full text |Cite
|
Sign up to set email alerts
|

Wolbachia enhances insect‐specific flavivirus infection in Aedes aegypti mosquitoes

Abstract: Mosquitoes transmit a diverse group of human flaviviruses including West Nile, dengue, yellow fever, and Zika viruses. Mosquitoes are also naturally infected with insect‐specific flaviviruses (ISFs), a subgroup of the family not capable of infecting vertebrates. Although ISFs are not medically important, they are capable of altering the mosquito's susceptibility to flaviviruses and may alter host fitness. Wolbachia is an endosymbiotic bacterium of insects that when present in mosquitoes limits the replication … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
34
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 109 publications
(173 reference statements)
0
34
0
Order By: Relevance
“…4). Although unanticipated, these results reflect the high degree of variability that exists across the Wolbachia phylogeny in terms of the interactions of this symbiont with other host viruses (33,64,65,81,(83)(84)(85). These effects on survival were shown not to be related to changes in viral accumulation (Fig.…”
Section: Discussionmentioning
confidence: 78%
“…4). Although unanticipated, these results reflect the high degree of variability that exists across the Wolbachia phylogeny in terms of the interactions of this symbiont with other host viruses (33,64,65,81,(83)(84)(85). These effects on survival were shown not to be related to changes in viral accumulation (Fig.…”
Section: Discussionmentioning
confidence: 78%
“…Perhaps the combination of protection of the RNA nucleocapsid genome or genome segments when released in the cytoplasm or activity of the RdRp aids in evasion of host immune response enhanced by Wolbachia or Wolbachia effector molecules (92). However, a recent study suggested increases in infection of A. aegypti mosquitoes by insect-specific flaviviruses when they harbor the Wolbachia wMel strain (93).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to IIT, Wolbachia has also been used for population replacement in various locations (8)(9)(10), as certain strains can spread to fixation while greatly reducing the vector's susceptibility to dengue virus (11). However, the literature suggests the effectiveness of different Wolbachia strains varies so far as to even enhance vector competence in some contexts, which may lead to a reevaluation of this technique (12)(13)(14)(15)(16)(17)(18). Therefore, there has been renewed interest in developing novel species-specific and cost-effective genetic technologies that provide long-lasting disease reduction with limited effort.…”
Section: Introductionmentioning
confidence: 99%